The Beneficial Effects of Ultramicronized Palmitoylethanolamide in the Management of Neuropathic Pain and Associated Mood Disorders Induced by Paclitaxel in Mice - Claudia Cristiano; Carmen Avagliano; Mariarosaria Cuozzo; Fabrizio Maria Liguori; Antonio Calignano; Roberto Russo (Biomolecules, 2022)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common complication of antineoplastic drugs, particularly paclitaxel (PTX). It can affect the quality of patients’ lives and increase the risk of developing mood disorders. Although several drugs are recommended, they yielded inconclusive results in clinical trials. The aim of the present work is to investigate whether the palmitoylethanolamide (PEA) would reduce PTX-induced CIPN and associated mood disorders. Moreover, the role PPAR-α and the endocannabinoid system will also be investigated. CIPN was induced by intraperitoneally injection of PTX (8 mg/kg) every other day for a week. PEA, 30 mg/kg, was orally administrated in a bioavailable form (i.e., ultramicronized PEA, um-PEA) one hour after the last PTX injection, for 7 days. In the antagonism experiments, AM281 (1 mg/kg) and GW6471 (2 mg/kg) were administrated 30 min before um-PEA. Our results demonstrated that um-PEA reduced the development of hypersensitivity with the effect being associated with the reduction in spinal and hippocampal pro-inflammatory cytokines, as well as antidepressive and anxiolytic effects. Moreover, the PPAR-α and CB1 receptor antagonists blocked the behavioral and antinociceptive effects of um-PEA. Our findings suggest that um-PEA is a promising adjunct in CIPN and associated mood disorders through the activation of PPAR-α, which influences the endocannabinoid system.